Causality in Economics: A Menu of Approaches - Pol, Eduardo (Journal of Reviews on Global Economics, 2013)
Causality is a notion that occurs often in economics. In using the words â€˜cause’ and â€˜effect,’ economists seek to distinguish causation from association, recognizing that causes are responsible for producing effects, whereas non-causal associations are not. The identification of causes is accorded a high priority because it is viewed as the basis for understanding economic phenomena and developing policy implications. In this survey we look at different approaches to causality in economics and set out the general principles of each approach, so as to assist in the communication and teaching role. Specifically, we confine attention to five approaches to causality in economics (narrative, comparative statics, theoretical, structural, and experimentalist) and elucidate their distinctive characteristics without entering into philosophical discussions. In particular, we pay close attention to the debate between the structuralist and experimentalist schools because this controversy has been extremely useful to clarify a number of fundamental points concerning causality in economics